PROBLEMS AND PROSPECTS OF THE DEVELOPMENT OF LIGHT INDUSTRY OF UKRAINE - Власенко, Ирина; Тернова, Алла (Modern engineering and innovative technologies, 2022)
The article shows that light industry is one of the strategic segments of the national economy. The development of Ukrainian light industry is constrained by unequal conditions of competition in the domestic market, instability of tax legislation, outdate